Giant simple hepatic cyst mimicking as hydatid cyst: diagnostic dilemma - R., Keerti; Manickam, Ramanathan; Gowthamen, Siddhartha (International Surgery Journal, 2021)
Giant liver cysts are uncommon. Hepatic cysts are usually asymptomatic and are found incidentally but they can become symptomatic and cause bleeding, infection, mass effect to adjacent structures or rupture. We described two cases of symptomatic liver cysts described suspected clinically and radiologically reported as hydatid cyst but were revealed to be simple liver cysts following surgery. Two elderly men presented with an enlarging abdominal mass and abdominal pain for 1 week. Both patients on radiology had large cysts in the liver causing significant mass effect on adjacent structures and characteristics were suggestive of hydatid cyst. Diagnostic laparoscopy with drainage was done for both patients and revealed as simple hepatic cyst. Hence simple liver cyst can mimic as hydatid cyst attaining giant dimensions and should be considered as an important differential diagnosis.